Evaluation of problem-based learning models in the integrated midwifery curriculum - Ari Indra Susanti; Rani Nurparidah; Ariyati Mandiri (Inovasi Kurikulum, 2024)
Evaluation of the Problem-Based Learning (PBL) model in the integrated curriculum aims to encourage midwifery students' learning abilities, evaluate the effectiveness of learning, and test students' abilities in midwifery knowledge. This article aims to evaluate the PBL model's evaluation in the integrated midwifery curriculum. The research method uses descriptive cross-sectional. Data was collected by administering content-validated questionnaires to 113 D4 Midwifery Study Program students, and then the univariate data was analyzed descriptively. The research results showed that the majority of students rated the implementation of the tutorial method and practice with lab activities, evaluation of theoretical learning with Multiple Choice Questions (MCQ) and Structure Oral Case Assessment (SOCA), and practice evaluation using the Direct Observation of Procedural Skills (DOPS) method. Apart from that, the majority of students agree that evaluation of field practice learning (clinic/community) can improve clinical abilities and advocacy skills across sectors (56.6%), and students are satisfied with lecturers as tutors during the learning process. This research concludes that the integrated curriculum uses tutorial learning strategies with MCQ and SOCA evaluations, thereby improving clinical and cross-sector advocacy skills based on student perceptions. AbstrakEvaluasi model Problem Based Learning (PBL) pada kurikulum terintegrasi bertujuan mendorong kemampuan belajar mahasiswa kebidanan, mengevaluasi keefektifan pembelajaran dan menguji kemampuan mahasiswa dalam pengetahuan kebidanan. Artikel ini bertujuan untuk mengetahui evaluasi model PBL pada kurikulum kebidanan terintegrasi. Metode penelitian menggunakan deskriptif dengan cross sectional. Pengumpulan data dilakukan dengan memberikan kuesioner yang telah tervalidasi content kepada 113 mahasiswa Program Studi D4 Kebidanan, kemudian data univariat dianalisis secara deskriptif. Hasil penelitian didapatkan sebagian besar mahasiswa menilai baik terhadap pelaksanaan metode tutorial dan praktik dengan lab activity, evaluasi pembelajaran teori dengan Multiple Choice Question (MCQ) dan Structure Oral Case Assesment (SOCA), dan evaluasi praktik dengan metode Direct Observation of Prosedural Skills (DOPS). Selain itu, sebagian besar mahasiswa setuju terhadap evaluasi pembelajaran praktik lapangan (klinik/komunitas) dapat meningkatkan kemampuan klinis dan keterampilan advokasi pada lintas sektor, serta mahasiswa puas terhadap dosen sebagai tutor saat proses pembelajaran. Simpulan pada penelitian ini bahwa kurikulum terintegrasi menggunakan strategi pembelajaran tutorial dengan evaluasi MCQ dan SOCA sehingga meningkatkan keterampilan advokasi klinis dan lintas sektor berdasarkan persepsi mahasiswa.Kata Kunci: Evaluasi; kurikulum terintegrasi; problem-based learning